Venous thrombosis in pregnant women: genetic and epigenetic risk factors - I. Elalamy (IRBIS LLC, 2019)
The most common cause of thrombosis isischemic heart attack, the second one is stroke, and the third one is venous thrombosis. According to European studies, venous thrombosis accounts for about 12 % of the population's deaths. The pathogenesis of thrombosis is well presented in the form of the Virchow's triad; that includes damage to the vascular endothelium, hypercoagulation and stasis. A pregnant woman is deficient in fibrinolytics and excessive in procoagulants. Pregnancy can be seen as a natural example of the Virchow's triad: the woman develops a state of hypercoagulation only because she is pregnant. Hypercoagulable state in pregnant women directly correlates with age, genetic thrombophilias, and autoimmune diseases. The formation of a blood clot may be associated with genetic factors, the so-called familial thrombophilias. This type of thrombophilia is caused by abnormalities in the genes that carry information about proteins involved in blood coagulation - proteins C and S, antithrombin III, Leiden mutation, prothrombin anomaly G 202110A. Thus, thrombosis is the result of an interaction between genetic and acquired risk factors or a combination of them. This is confirmed by the RIETE data registry. It is highly advisable to identify patients at risk and determine the strategy of managing these patients with the least dangerous consequences.